2016
DOI: 10.1002/jtr.2080
|View full text |Cite
|
Sign up to set email alerts
|

Existential Authenticity and Anxiety as Outcomes: The Tourist in the Experience Economy

Abstract: The idea of meaning‐making as embedded in the experience economy 3.0 implies that greater consumption does not lead to greater contentment, and thus, products that have the capacity to meaningfully transform a consumer are to constitute the ultimate economic offering. Conceptualizing transformation as changes in tourist existential authenticity and anxiety, this study investigates the effect of tourism on these existential dimensions. Utilizing the survey data, we find positive effects and discover that percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 61 publications
4
83
0
3
Order By: Relevance
“…The tourism system is changing from 'economy' to an 'experience economy' where tourists' seek a more personal and transformational experience (Kirillova, Lehto & Cai, 2016). Thus a different perspective is needed to better adapt to the current trends.…”
Section: Introductionmentioning
confidence: 99%
“…The tourism system is changing from 'economy' to an 'experience economy' where tourists' seek a more personal and transformational experience (Kirillova, Lehto & Cai, 2016). Thus a different perspective is needed to better adapt to the current trends.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the experiential aspects of authenticity has garnered considerable attention in the last decade. While Bruner (1991) describes tourists' desire for self-transformation through an encounter with 'authentic' cultures, more recently scholars examine the ways tourists understand authentic experiences and their own Being while on holiday (Belhassen, Caton, & Stewart, 2008;Brown, 2013;Buchmann, Moore, & Fisher, 2010;Kim & Jamal, 2007;Kirillova et al, 2016Kirillova et al, , 2017Rickly-Boyd, 2012b, 2013bVidon & Rickly, 2018;Wang, 1999;Wassler & Kirillova, 2019). Existential authenticity refers to an experience that involves a sense of self identity activated by the liminality of tourism and informed by both interpersonal (family ties, communitas) and intrapersonal dimensions (bodily feelings, self-making) (Wang, 1999).…”
Section: Death Existential Authenticity and Existential Anxietymentioning
confidence: 99%
“…In tourism studies, anxiety is discussed in relation to motivation (see Brown, 2013;Canavan, 2017;Kirillova et al, 2016;Shepherd, 2015;Vidon & Rickly, 2018). While Dann (1977) was among the first to note the implications of 'anomie' for touristic motivation, the concept received little attention until the last decade.…”
Section: Existential Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Reisinger and Steiner (2006) came to the conclusion that existential authenticity affects tourists' existential anxiety once they have returned home. Furthermore, the meaningfulness of their experience is determined by the value the tourists themselves place on the experience (Kirillova, Lehto, and Cai 2017). Park, Choi, and Lee (2019) found that objective authenticity does not influence loyalty, while constructive authenticity affects both existential authenticity as well as tourist satisfaction.…”
Section: Authenticitymentioning
confidence: 99%